Bilateral aneurysmal bone cyst of maxilla (Tanzania Medical Journal, 2009)
Aneurysmal bone cyst (ABC) is an uncommon benign lesionoriginating in the craniofacial region and has seldomly beenreported in Tanzania and other parts of the world. Between 2-12%of ABC are located in the head and neck region and 90% are foundin the posterior mandible while less than 1% of the cysts are biopsedin the maxilla. In this study we report a case of ABC arising fromboth maxilla of a 19-years old African man as revealed by bothroentgenographic and microscopic findings. The presentingsymptoms of our patient were mainly painless swelling, difficult inchewing and closing the mouth. Extra-oral examination revealeddifficult in closing the mouth, a large pinkish swelling protrudingfrom the mouth and ulcerations on left and right side of the maxilla.The submandibular and submental lymph nodes were palpablebilaterally and were mobile. Intra-orally, the swelling involved thewhole of left and right maxillary alveolar process. Only 48, 46, 45were present on the mandible while the rest of the teeth weremissing. Teeth marks were seen on the swelling. The swelling wasbony hard on palpation and the gingivae had grown to reach thebuccal sulcus and the palatal midline.The aetiology andpathogenesis of this interesting lesion remained unclear but severaltheories were reviewed and the differential diagnosis of the lesionwas also discussed.The treatment of choice of the case we performed was surgicalexcision and curettage of the cavity of the ABC, which is the goldstandard, let alone many other treatment options. The treatmentwas directed towards complete removal of the lesion. Beforeentering, the lesion was adequately exposed to enable a rapidcurettage to be done. Massive bleeding was encountered as soon asthe lesion was entered and continued until complete curettage wasaccomplished and there was no further bleeding. The patient had aremarkable post-operative period and the outcome of the treatmentwas very good.Key words: Aneurysmal, bone cyst, Maxilla, Craniofacialregion, Curettage.